Linear-dendrimer type methoxy-poly (ethylene glycol)-b-poly (ε-caprolactone) copolymer micelles for the delivery of curcumin. (January 2015) - Song, Zhimei; Zhu, Wenxia; Song, Jiarong; Wei, Peng; Yang, Fengying; Liu, Na; Feng, Runliang
Abstract Purpose: To improve curcumin's pharmacokinetic, in vitro cytotoxicity and release property. Methods: A novel linear-dendrimer methoxy-poly (ethylene glycol)-b-poly (ε-caprolactone) copolymer was synthesized through O-alkylation, basic hydrolysis and ring-opening polymerization reaction with methoxy-poly (ethylene glycol), epichlorohydrin and ε-caprolactone as raw materials. Its structure was characterized by 1H-NMR and GPC. The copolymer's hemolysis and micellar encapsulation for curcumin by thin-film hydration were studied. Curcumin-loaded micelles were evaluated by use of in vitro release, FT-IR and X-ray diffraction. Curcumin-loaded micelles' in vitro cytotoxic activities against Hela and HT-29 cells were done, and its pharmacokinetic parameters were also carried out. Results: Curcumin was encapsulated into the micelles with 92.54% of entrapment efficiency and 12.84% of drug loading in amorphous forms. The dissolubility of nanoparticulate curcumin was 1.70 × 105 times higher than that of curcumin in water. The obtained copolymer showed no hemolysis. In vitro drug release study indicated that, in all cases, the kinetics was adjusted well to the Makoid–Banakar model ( <![CDATA[ opagenumbers R_abj^2 ]]> = 0.9984). In addition, data were analyzed by the Korsmeyer–Peppas model, n values were 0.43, indicating that the drug release was accomplished by the combination diffusion and polymer chain relaxation. The cytotoxicity experiment indicated that the nanoparticulate curcumin kept up its potent anti-cancer activities. The pharmacokinetic results showed that the MRT0–∞, t1/2z and AUC0–∞ of Curcumin-loaded micelles were 1.64, 6.54 and 4.67 times higher than that of CUR control solution. Conclusions: The copolymeric micelles loading curcumin might act as a delivery vehicle for CUR.